Optimal soft-switching scheme for bidirectional DC-DC converters with auxiliary circuit - Lee, Han Rim; Park, Jin Hyuk; Lee, Kyo Beum (Journal of Power Electronics, 2018)
This paper proposes a soft-switching bidirectional dc-dc converter (BDC) with an auxiliary circuit. The proposed BDC can achieve the zero-voltage switching (ZVS) using an auxiliary circuit in the buck and boost operations. The auxiliary circuit supplies optimal energy for the ZVS operation of the main switches. The auxiliary circuit consists of a resonant inductor, a back-to-back switch and two capacitors. A small-sized resonant inductor and an auxiliary switch with a low-rated voltage can be used in the auxiliary circuit. Zero-current switching (ZCS) turn-on and turn-off of the auxiliary switches are possible. The proposed soft-switching scheme has a look-up table for optimal switching of the auxiliary switches. The proposed strategy properly adjusts the turn-on time of the auxiliary switch according to the load current. The proposed BDC is verified by the results of PSIM simulations and experiments on a 3-kW ZVS BDC system.
Keywords: Auxiliary circuits; Auxiliary switch; Bidirectional dc dc converters (BDC); Bidirectional DC-DC converters; Look up table; Optimal switching; Rated voltages; Resonant inductors; Auxiliary circuit; Bidirectional dc-dc converter (BDC); Look-up table; Soft switching; Zero-voltage switching